Plasma exchange activity in the European Union. (June 2019) - Lozano, Miquel; Rivero, Andrea; Cid, Joan
Abstract: In spite of a relatively high number of diseases where therapeutic plasma exchange (TPE) is recommended as a first (category I) or second line of therapy (category II), according to the Guidelines on the Use of Therapeutic Apheresis in Clinical Practice-Evidence-Based Approach from the American Society for Apheresis, evidence exists that the number of procedures that are performed varies widely depending on the countries and even between centers in a given country. The aim of this work was to analyze the number of TPE that are performed in different European countries and calculate the rate of TPE per 1, 000, 000 inhabitants. We contacted the three manufacturers of disposables for performing TPE by centrifugation in Europe (Fresenius Kabi, Haemonetics, and Teurmo BCT) and asked them for the number of disposables sold in each of the countries of the European Union (EU) in 2014 as a surrogate indicator of the TPE performed in the country. A total of 101, 767 disposable units to perform TPE using centrifugation devices were sold in the EU in 2014. A huge variation exists in the number of disposable units of PTE sold in the different EU countries. A factor of 51 separates the rate of TPE per 1 million inhabitants performed by centrifugation in the country with the highest number (Belgium, 459) from the country with the lowest (Romania, 9). That variation probably is due to differences in healthcare expenditure but also differences in practice.